Feast of fools - Caine, Rachel (New York : NAL Jam Books, 2008)
The college town of Morganville is filled with vampires and humans who have learned to live in relative peace, but when old-school vampire Mr. Bishop arrives, his desire to dominate threatens the town's peace, and it is up to student Claire Danvers to stop his evil plan before he can trap the humans of Morganville and feast on their flesh.
Adult
Keywords: College students -- Fiction; Good and evil -- Fiction; Vampires -- Fiction; College students -- Fiction; Good and evil -- Fiction; Vampires -- Fiction; Fantastic fiction